Developing Future Physical Education Teachers' Intercultural Competence: The Potential of Intertwinement of Transformative, Embodied, and Critical Approaches - Mariana Elisabet Siljamäki (Frontiers Media S.A., 2021)
Purpose: This article is based on a study that explored learning processes related to intercultural competence of PE teacher trainees. The context of the study was the Faculty of Sport and Health Sciences at the University of Jyväskylä, Finland. The study was conducted in connection to two courses that focused on equality in physical education and sport in 2020–2021.Methods: Adopting an interpretive, as well as a critical approach, the authors focused on how the students described their conceptions and learning experiences. Based on their analysis they have then aimed to shed light on how interculturality, equality, equity, and diversity may be addressed in higher education in a more profound manner. The students' accounts were analyzed first through an open reading and subsequently through a more critical lens. The analysis was supported by theories of transformative learning, embodied learning, and intercultural education.Results: Students' initial interest toward equity, equality, and interculturality seemed to expand during the courses. They increasingly reflected on the complexity of these issues and discussed the widening professional responsibilities of future PE teachers in promoting equality and supporting pupils in cultural heterogeneous classes. Discussions and practical activities that involved emotional and embodied elements seemed to be important in facilitating their learning processes. However, it is difficult to foresee how permanent the changes in their habits of mind and subsequent actions are.Discussion: The authors suggest that embodied, practical approaches where the student is fully engaged in the learning process, and where conceptual, reflective, emotional, and affective levels are connected, may be a key in developing teachers' intercultural competence. They also suggest that it is crucial to revise higher education curricula from the perspectives of intercultural competence and structural inequality. In addition to separate courses, equality, equity, and diversity should be seen as red threads throughout higher education.